Romano Del Nord. Teoria e prassi del progetto di architettura - BOLOGNA, ROBERTO (Saggi. Architettura, Pianificazione, Paesaggio, Design, 2021)
Romano Del Nord has been a point of reference for Architectural Technology and a protagonist in academic research and the realization of building programs. Meditating on his work brings out the relationship between research, cultural and social commitment and realization skills that distinguished his mindset and his way of acting. The book offers a reasoned rereading of his writings, drawn from books, articles and conferences, chronologically ordered and grouped around some areas most performed by Del Nord: the building process, the places for education, the spaces for health care. A rereading tracing the years when the discipline of architectural design for the community established itself, scientifically founded and attentive to resources and contexts. His words testify to the vision which accompanied his commitment, in the years between the 20th and 21st centuries, on the relationship between research and design, training and society, innovation and building processes, strategies and policies.